2015
DOI: 10.1371/journal.ppat.1004868
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Small Non-AUG-Initiated ORF in Poleroviruses and Luteoviruses That Is Required for Long-Distance Movement

Abstract: Viruses in the family Luteoviridae have positive-sense RNA genomes of around 5.2 to 6.3 kb, and they are limited to the phloem in infected plants. The Luteovirus and Polerovirus genera include all but one virus in the Luteoviridae. They share a common gene block, which encodes the coat protein (ORF3), a movement protein (ORF4), and a carboxy-terminal extension to the coat protein (ORF5). These three proteins all have been reported to participate in the phloem-specific movement of the virus in plants. All three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 87 publications
4
124
1
Order By: Relevance
“…It has been reported that polerovirus PLRV contains three subgenomic RNAs (sgRNAs) at 3′-region of viral RNA5152. Translation of sgRNA1 enables expression of ORFs 3a, 3, 4, and 54153, while that of sgRNA2 codes two proteins at the 3′-region of ORF551. The recently identified sgRNA3 encodes a RNA-binding protein52.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that polerovirus PLRV contains three subgenomic RNAs (sgRNAs) at 3′-region of viral RNA5152. Translation of sgRNA1 enables expression of ORFs 3a, 3, 4, and 54153, while that of sgRNA2 codes two proteins at the 3′-region of ORF551. The recently identified sgRNA3 encodes a RNA-binding protein52.…”
Section: Discussionmentioning
confidence: 99%
“…Translation initiation at Leu 59 would create a polypeptide of 40 amino acids, which would make it the shortest described IAV polypeptide, but still possibly functional. M42, a splice variant of M2, is 54 residues in length, (48), and a functional 45-residue protein has been defined in Luteroviradae (49). Our findings imply that translation can be also be initiated at Leu 96, which would create a 2 amino acid gene product before the stop codon at position 98--surely too short to be functional.…”
Section: Discussionmentioning
confidence: 99%
“…1). All luteoviruses and poleroviruses contain a 45 – 50 codon ORF (ORF3a) beginning with a non-AUG codon (AUU, AUA, ACG, or CUG depending on the virus) and terminating between the start codons of ORFs 3 (CP ORF) and ORF 4 (Smirnova et al, 2015). [WAM7] Owing to the lack of an AUG codon, ORF 3a is translated at low levels, so most ribosomes (40S subunits) do not initiate at the ORF3a start codon and continue to scan until they initiate translation at the ORF 3 (CP) or ORF4 start codon.…”
Section: Translational Controlmentioning
confidence: 99%